Ф. М. Достоевский – 200 лет со дня рождения: Восприятие его творчества в Норвегии сто лет тому назад - Egeberg, Erik (Poljarnyj vestnik, 2021)
This article explores two Norwegian publications related to Dostoevskij, both of which were published in 1922. In his doctoral dissertation, Martin Gran, who was the first scholar in Norway to defend a dissertation in the field of Slavic studies, discussed the works of the young Dostoevskij. The second publication under scrutiny is Erik Krag’s novel Ottar Wreike, which shows influence from Dostoevskij’s Raskol’nikov.